(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2015)
It is evident that archaeological artefacts are subject to significant risks for many reasons, but mainly due to their vulnerability and to environmental danger, as they are generally consisting of ruined structures, often in an advanced state of decay and directly exposed to the weathering. To adequately take under control the risk factors, in order to avoid the inevitable loss of archaeological artifacts, or at least to lengthen their life cycle in the best storage conditions, constant monitoring activities and interventions for prevention are required, as well as protection and "cure", assiduous and continued over time. In recent years, on the basis of a significant experimental phase, developed on excellence cases, effective operational tools have been made, which define procedures directed to the activation of processes of inspection activities (controls) and preventative maintenance. These experiences have also shown that the preservation of cultural heritage, as well as of archaeological artefacts, requires attention and interventions for which it is not always necessary to rely on archaeological skills, but simply on common sense and technical knowledge of the rules of arts and building best practices, already widely known and tested. Without underestimating, therefore, the importance of expertise, as an essential condition to allow the recognition of value, and from that learning the necessary precautions in operating, it must be considered that the conditions of decay, most often caused by lacking or wrong maintenance, are not usually due to limitations in scientific or technical knowledge, but to weakness and omissions in prevision, organisation and planning.